Tackling orientation of metal-organic frameworks (MOFs): The quest to enhance MOF performance - Khalil, Islam E.; Fonseca, Javier; Reithofer, Michael R.; Eder, Tanja; Chin, Jia Min (Coordination chemistry reviews, 2023)
•A comprehensive Review of the methods for preparing oriented MOFs.•Control of MOF orientation helps to maximize their performance.•Secondary growth and evolutionary selection can lead to oriented MOFs.•Dynamic alignment of free-standing MOFs can be achieved using external fields.•The use of free-standing MOFs is a new approach to creating aligned MOF assemblies.•The advantages of oriented MOFs over their randomly oriented counterparts are reported. As the structure and properties of anisotropic metal–organic frameworks (MOFs) vary with certain directions in space, controlling the orientation of these MOFs allows full advantage to be taken of their anisotropic properties. Not surprisingly, the preparation of oriented anisotropic MOFs, has drawn great attention in the past decade. In this review, we systematically summarized the strategies utilized for the preparation and growth of oriented MOFs, highlighting the possibilities of each synthetic approach as well as the challenges they have to overcome. Herein, we have also explored the orientation of MOF-on-MOF hybrids. Finally, we have presented the advantages of oriented MOF crystals over their randomly oriented counterparts in different applications, including adsorptions, separations, catalysis, sensing, energy storage, etc. We hope this review shows the tremendous possibilities of oriented MOFs and helps the reader better comprehend oriented MOF synthesis, properties, and applications.